2022
DOI: 10.1186/s12877-022-02968-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral health and frailty: results from the Korea National Health and Nutrition Examination Survey

Abstract: Background Previous research has suggested that poor oral health is positively associated with frailty. The objective of this study was to explore associations of key oral diseases (periodontal disease, tooth loss), and oral hygiene and management behaviors with the level of frailty in community-dwelling older Korean adults using national representative survey data. Methods This study used cross-sectional, 6th and 7th Korea National Health and Nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Periodontal disease is an inflammatory process that can lead to elevated levels of gingival epithelial inflammatory markers interleukin, tumor necrosis factor-alpha, and histamine, which amplify inflammation and may lead to the progression of frailty [ 17 ]. Other oral health indicators, i.e., oral function, self-rated oral health, brushing habits, oral pain and masticatory dysfunction were significantly associated with frailty [ [47] , [48] , [49] , [50] ]. The intrinsic mechanisms by which oral health contributes to frailty in older adults include five main aspects: malnutrition, chronic inflammation, cognitive function, psychosocial factors, and neural pathways [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease is an inflammatory process that can lead to elevated levels of gingival epithelial inflammatory markers interleukin, tumor necrosis factor-alpha, and histamine, which amplify inflammation and may lead to the progression of frailty [ 17 ]. Other oral health indicators, i.e., oral function, self-rated oral health, brushing habits, oral pain and masticatory dysfunction were significantly associated with frailty [ [47] , [48] , [49] , [50] ]. The intrinsic mechanisms by which oral health contributes to frailty in older adults include five main aspects: malnutrition, chronic inflammation, cognitive function, psychosocial factors, and neural pathways [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, systemic health plays a significant role in oral health-related practices. Older adults living in institutions often exhibit a greater burden of systemic health issues, including chronic diseases [25] and cognitive decline [20,26], which impede their ability and inclination to undertake appropriate self-care oral practices, consequently elevating the risk of dental caries. Third, mobility restrictions and financial constraints commonly encountered by institutionalised elderly people usually hinder their ability to obtain timely and suitable oral healthcare interventions, thereby leaving dental caries untreated or unaddressed.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tuuliainen et al found that the brushing frequency among Finnish frail older inhabitants remained significantly lower than in the non-frail older adults, and positive changes in the prevalence of brushing teeth twice a day were observed [ 44 ]. In 2022, a study from communities in South Korea found that brushing after all three meals was negatively correlated with frailty among older adults aged 50 years or older [ 45 ]. Additionally, insufficient brushing has been shown to frailty-related enabling factors [ 46 ].…”
Section: Discussionmentioning
confidence: 99%